The prevalence and pattern of deciduous molar hypomineralization and molar-incisor hypomineralization in children from a suburban population in Nigeria. - Temilola, Oluwaseyi Dada; Folayan, Morenike Oluwatoyin; Oyedele, Titus (BioMed Central, 2024)
6p.